Telaah Konseptual Ilmu ‘Ilal al-ḥadīṡ: A Conceptual Study of the Science of ‘Ilal al-ḥadīṡ - Sofyan Nur; Irwan Fitri Aco (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
This study aims to examine the essence of the Science of 'Ilal al-Hadith, covering its historical development as a scientific discipline, its scope, its urgency, as well as its pioneering figures and developers. This research employs a library research method focusing on the study of manuscripts and texts from various literature of Hadith studies. It utilizes historical, philosophical, and hadithi (hadith-technical) approaches. Results: The results of this study indicate several key findings: First: Historically, the Science of 'Ilal al-Hadith does not have extensive records regarding its early development as a formal discipline. Its origins can only be traced through limited accounts of hadith criticism activities carried out by early scholars, such as Imam Syu’bah bin al-Hajjaj. Second: The scope of 'Ilal al-Hadith focuses on hadiths narrated by thiqah (trustworthy/reliable) narrators, with the aim of uncovering hidden flaws or errors ('ilal) that may occur even among reliable narrators. Regarding its urgency, this science represents the pinnacle of Hadith studies—being the most extensive, detailed, and vital branch. Third: This discipline was developed by prominent hadith scholars who dedicated their lives to advancing the science of 'ilal and hadith sciences in general. The implications of this research include providing a clear description of the nature of 'Ilal al-Hadith, which is fundamentally still misunderstood by many students of knowledge. Furthermore, it clarifies the specific field of 'ilal within the broader family of Hadith sciences, thereby providing scientific insight for anyone, particularly for students and researchers in this field.